The oxygen dilemma: The challenge of the anode reaction for microbial electrosynthesis from CO2 - Abdollahi, Maliheh; Al Sbei, Sara; Rosenbaum, Miriam A.; Harnisch, Falk (Frontiers in Microbiology, 2022)
Microbial electrosynthesis (MES) from CO2 provides chemicals and fuels by driving the metabolism of microorganisms with electrons from cathodes in bioelectrochemical systems. These microorganisms are usually strictly anaerobic. At the same time, the anode reaction of bioelectrochemical systems is almost exclusively water splitting through the oxygen evolution reaction (OER). This creates a dilemma for MES development and engineering. Oxygen penetration to the cathode has to be excluded, while assuring low resistance. We will show that this dilemma derives a strong need to identify novel reactor designs when using the OER as anode reaction or to fully replace OER by alternative oxidation reactions.